2010
DOI: 10.1007/s12110-010-9094-0
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Aggression among Aka Hunter-Gatherers of the Central African Republic

Abstract: This paper explores sex differences in interpersonal aggression among Aka foragers of the Central African Republic (CAR). We tested whether male Aka physically aggressed more than female Aka, and whether female Aka indirectly aggressed more than male Aka, as evolutionary theories of aggression predict. To our knowledge, these are the first tests of these theories among an extant population of hunter-gatherers. We also tested predictions of a recent evolutionary theory of physical strength, anger, and physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 26 publications
2
36
0
Order By: Relevance
“…The most important of which, is an evolutionarily derived explanation for the data showing an association between fWHR and a variety of male dominant behaviors (Carré & McCormick, 2008;Stirrat & Perrett, 2010;Stirrat et al, 2012). This interpretation, which awaits empirical testing, is supported by the robust multicultural evidence that fighting ability is associated with physical aggression and success in interpersonal conflicts (Archer & Thanzami, 2007;Gallup, White, & Gallup, 2007;Hess, Helfrecht, Hagen, Sell, & Hewlett, 2010;Von Rueden, Gurven, & Kaplan, 2008) as well as studies on a non-human primate (i.e. The studies reported herein were not designed to test the hypothesis that the effect of fWHR on aggressiveness is mediated by fighting ability; however, it is plausible that the relationship between fWHR and aggression that has been found in previous studies (though not always consistently, see Ozener, 2012) is most likely due to the fact that fWHR predicts fighting ability, and that males with greater fighting ability exhibit more anger and aggression.…”
Section: Discussionmentioning
confidence: 93%
“…The most important of which, is an evolutionarily derived explanation for the data showing an association between fWHR and a variety of male dominant behaviors (Carré & McCormick, 2008;Stirrat & Perrett, 2010;Stirrat et al, 2012). This interpretation, which awaits empirical testing, is supported by the robust multicultural evidence that fighting ability is associated with physical aggression and success in interpersonal conflicts (Archer & Thanzami, 2007;Gallup, White, & Gallup, 2007;Hess, Helfrecht, Hagen, Sell, & Hewlett, 2010;Von Rueden, Gurven, & Kaplan, 2008) as well as studies on a non-human primate (i.e. The studies reported herein were not designed to test the hypothesis that the effect of fWHR on aggressiveness is mediated by fighting ability; however, it is plausible that the relationship between fWHR and aggression that has been found in previous studies (though not always consistently, see Ozener, 2012) is most likely due to the fact that fWHR predicts fighting ability, and that males with greater fighting ability exhibit more anger and aggression.…”
Section: Discussionmentioning
confidence: 93%
“…face, and voice , and respond to these cues by calibrating welfare tradeoff ratios such that males who are better fighters are expected -by themselves and others -to receive greater consideration (Delton & Sell, 2014;Hess, Helfrecht, Hagen, Sell, & Hewlett, 2010;Lukaszewski, 2013;Petersen, Sznycer, Sell, Cosmides, & Tooby, 2013;Pietraszewski & Shaw, 2015;Thomsen, Frankenhuis, Ingold-Smith, & Carey, 2011). Similar cue-based computational systems underlie reciprocity, prestige and deepengagement friendships that calibrate welfare tradeoff ratios to the ecology of human cooperation (Delton & Robertson, 2016;Kirkpatrick, Delton, Robertson, & de Wit, 2015;Komorita, Parks, & Hulbert, 1992;Petersen, Sell, Tooby, & Cosmides, 2012;Sznycer et al, 2012;Tooby & Cosmides, 1996).…”
Section: The Computational Structure Of the Welfare Tradeoff Functionmentioning
confidence: 99%
“…Chest compression strength is a representative measure of male upper-body strength, a key component of fighting capacity; correspondingly, this measure predicts conflictual self-interested attitudes (Sell et al 2009a;Hess et al 2010;Sell et al 2012). …”
Section: Materials and Proceduresmentioning
confidence: 99%
“…Correspondingly, by attending to such features, observers appear able to accurately judge a man's strength and fighting ability (Sell et al 2009a;Sell et al 2010;Třebický et al 2013). Moreover, male morphology appears to be adaptively complemented by a corresponding psychology, as men who are stronger / better fighters report greater feelings of entitlement, lower tolerance for imposed costs, and greater use of and endorsement of violent or coercive tactics, with physical strength being a determinant of each (Gallup et al 2007;Archer and Thanzami 2009;Sell et al 2009b;Hess et al 2010;Sell et al 2012;Muñoz-Reyes et al 2012;Petersen et al 2013; but see also Price et al 2012 for caveats). These sentiments 6 reveal a motivational architecture attuned to the likelihood of victory in violent conflict, one that must necessarily be based on assessments of relative formidability.…”
mentioning
confidence: 99%
See 1 more Smart Citation